Rotational atherectomy and new‐generation drug‐eluting stent implantation. Issue 6 (5th December 2017) - Hachinohe, Daisuke; Kashima, Yoshifumi; Kanno, Daitaro; Kobayashi, Ken; Sugie, Takuro; Kaneko, Umihiko; Tadano, Yutaka; Watanabe, Tomohiko; Shitan, Hidemasa; Fujita, Tsutomu
Abstract: Objectives: The aim of this study was to evaluate the clinical outcomes of rotational atherectomy (RA) followed by new‐generation drug‐eluting stent (DES) implantation in patients with an extensive amount of calcified and fibrotic plaque. Background: RA followed by new‐generation DES implantation for complex lesions has not been thoroughly evaluated. Methods: A total of 744 consecutive patients (770 lesions) treated with new‐generation DES implantation following RA for de novo lesions between January 2013 and November 2015 were retrospectively identified using our institutional database. Clinical outcomes at 12 months were evaluated and the independent predictors of all‐cause death and target vessel failure (TVF) were assessed using Cox regression models. Results: Target lesion revascularization occurred in 22 lesions (2.9%) and TVF occurred in 51 lesions (6.6%). In a multivariate analysis, hemodialysis, non‐ST‐segment elevation acute coronary syndrome, low ejection fraction, and HbA1c ≧ 7% were associated with 12‐month mortality. Hemodialysis and right coronary artery were identified as independent predictors of TVF (hazard ratio (HR) 4.107, 95% confidence interval (CI) 2.194‐7.685, P  < .001; HR 2.491, 95% CI 1.023‐6.062, P  = .044, respectively). Conclusions: A good debulking with RA followed by new‐generation DES implantation is recommended for patients with an excessive amount of calcified and fibrotic plaque, as this will likely improve the clinical outcomes.